Avoiding OCL specification pitfalls - Chiorean, Dan; Ober, Ileana; Petrascu, Vladiela (Electronic Communications of the EASST, 2012)
This paper discusses about teaching software modeling by using OCL specifications, in the context in which the web represents the main source of information. The raise of the interest for models induced a higher need for clear and complete specifications. In case of models specified by means of MOF-based languages, adding OCL constraints proved to be an interesting answer to this need. Several OCL examples posted on web include hasty specifications, that are often dissuasive with respect to complementing models with OCL specification. OCL beginners, and not only, need to know how to avoid potential specification traps. Our proposal is based on a complete and unambiguous description of requirements, that represents the first step towards good OCL specifications. The work highlights several major aspects that need to be understood and complied with to produce meaningful and efficient OCL specifications. This approach was tested while teaching OCL at Babes-Bolyai University of Cluj-Napoca.